(untitled) (Research, Society and Development, 2021)
Tooth and palate development share several molecules during their formation, which could explain some recent studies suggesting that tooth agenesis is associated with palatine rugae pattern. Therefore, the purpose of the se cross sectional study was to investigate the association between palatine rugae phenotypes and tooth agenesis in Brazilian patients. After applying inclusion and exclusion criteria 83 records from orthodontic patients were evaluated. Tooth agenesis cases were diagnosed by evaluation of panoramic radiographs and by anamnesis. The casts and intraoral occlusal photography of each patient were used to evaluated the palatine rugae according to length, shape, direction and unification. All analyses were performed by the same calibrated examiner. All tests were performed with an established alpha of 0.05 (P ≤ .05). Odds ratio calculations and chi-square or Fisher exact tests were used in the statistical analysis. A total of 17 (20.7%) patients with tooth agenesis was observed. The predominant shape of rugae was wavy (66.3%). The absence of secondary or fragmentary rugae was associated with tooth agenesis (p = 0.047; Odds ratio=3.00, Confidence Interval 95%=1.03-9.53). In conclusion, patients with tooth agenesis present a different palatine rugae pattern. The absence of secondary or fragmentary rugae was associated with isolated tooth agenesis in the population studied.